Collaborative governance in empowering women in coastal areas in Bekasi regency - Rahayu, Susi Dian; Nurjannah, Annisa Eka (Priviet Social Sciences Journal, 2025)
Collaborative governance is an appropriate concept for building community development through community empowerment. Empowerment activities are a good first step in building a strategy to achieve increased community welfare and the abilities of people who experience inadequate living. Segarajaya Village is a coastal village, and the majority of coastal communities have educational, social, and economic limitations. Women’s empowerment increases the skills and strengths that women have so that they can become independent and creative. This study aims to analyze how collaborative governance empowers women in Segarajaya Village through the Seraci batik craftsmen group. The theory used in this research is the collaboration theory from Ansel and Gash, which suggests that there are four indicators that influence the implementation of collaboration: initial conditions, institutional design, facilitative leadership, and collaborative process. This study uses qualitative research methods, with a descriptive approach. The results of this research show that the collaborative process of empowering women in coastal areas through the Seraci batik craftsman group in Segarajaya Village has gone quite well, although the implementation of collaborative governance is still not running optimally. Existing collaboration tends to be less flexible, lacks trust, and is dominated by the private sector, which becomes an obstacle to collaboration, resulting in the implementation of collaborative governance not being optimal.